The Effect of Profitability on Firm Value: The Role of Firm Size and Economic Crisis (2008–2024) - Hidayat, Yosep Rahman; Mahpudin, Endang; Mayasari, Mayasari (Almana : Jurnal Manajemen dan Bisnis, 2025)
Profitability is a key indicator of a company’s financial performance, influencing investor confidence and market valuation. However, its effect on firm value may vary depending on internal characteristics and external economic conditions. This study aims to analyze the effect of profitability on firm value by examining the moderating roles of firm size and economic crisis. Using a quantitative approach with moderated regression analysis, the research utilizes panel data from 2,050 companies listed in the Forbes Global 2000 during 2008–2024, resulting in 33,963 firm-year observations across multiple sectors and countries. Firm value is measured by market value (log-transformed), profitability by return on assets (ROA), and moderating variables include firm size and economic crisis, both measured as dummy variables. The results show that profitability significantly affects firm value, with a stronger impact for larger firms and a weaker impact during economic crises. Interaction analysis reveals that high profitability mitigates the negative effects of crises on firm value, indicating its role as a resilience factor. These findings highlight that the profitability–firm value relationship is contingent upon both internal attributes and macroeconomic conditions, offering insights for managers and investors in aligning strategic decisions with organizational capacity and prevailing economic environments.